2010
DOI: 10.1039/c001219j
|View full text |Cite
|
Sign up to set email alerts
|

Aluminosilicates with varying alumina–silica ratios: synthesis via a hybrid sol–gel route and structural characterisation

Abstract: Aluminosilicates with varying Al2O3:SiO2 molar ratios (3:1, 3:2, 3:3 and 3:4) have been synthesized using a hybrid sol-gel route using boehmite sol as the precursor for alumina and tetraethyl orthosilicate (TEOS) as the precursor for silica. The synthesis of boehmite sol from aluminium nitrate, and its use as the alumina precursor, is cost effective compared to alkoxide precursors. Structural aspects, including bonding and coordination, are studied in detail for samples calcined in the temperature range 400-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 43 publications
3
25
0
Order By: Relevance
“…4 , and the corresponding assignments are listed in Table 1 . The IR spectra of our samples are similar to those reported for natural and synthetic silica/alumina composites [ 29 37 ]. In the wavenumber range of 400–1300 cm −1 , nine, obvious, characteristic, IR peaks from the composite samples are observed and are located at 475, 530, 573, 618, 730, 790, 848, 878, and 1120 cm −1 .…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…4 , and the corresponding assignments are listed in Table 1 . The IR spectra of our samples are similar to those reported for natural and synthetic silica/alumina composites [ 29 37 ]. In the wavenumber range of 400–1300 cm −1 , nine, obvious, characteristic, IR peaks from the composite samples are observed and are located at 475, 530, 573, 618, 730, 790, 848, 878, and 1120 cm −1 .…”
Section: Resultssupporting
confidence: 83%
“…The IR peak at ≈475 cm −1 is due to the vibrations of O–Si–O bending modes (SiO 4 ), whose intensity increases with an increase in the Si content. Typically, the stretching modes of an AlO 6 moiety are expected in the region 500–680 cm −1 , whilst comparable modes for AlO 4 appear in the region of 680–880 cm −1 [ 29 30 ]. Thus, the characteristic, broad adsorption peaks at 530, 575, and 618 cm −1 are assigned to Al–O stretching modes (AlO 6 ), and the peaks at 730, 848, and 878 cm −1 are due to the vibrations of Al–O stretching modes (AlO 4 ) [ 31 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…When the sintering temperature was further increased to 1400 °C (Figure 4c) a substantial change in crystallinity of the sample was observed, as characterized by sharp increase of mullite phase and diminish of quartz as well as alumina phase, suggesting that both quart and alumina have completely transformed into mullite. In previous studies 30,31,32 , it has been reported that at temperature around 1400 °C, quartz was converted into liquid silica which penetrated alumina grain aggregates, and the two reacted to produce mullite. This is in good agreement with this study where mullite was the major phase present at 1400 °C.…”
Section: B Phase Development Studiesmentioning
confidence: 99%
“…Hence as the practical use of aluminosilicates increases so does the number of research papers dealing with the phase equilibria that occur in the SiO 2 -Al 2 O 3 binary system (in which mullite is the intermediate phase) and with the mechanism and kinetics of crystalline mullite formation [1][2][3]. However, the phase equilibrium diagrams found in the literature differ depending on the source.…”
Section: Introductionmentioning
confidence: 99%